Preparation and study of poly vinyl alcohol/hyperbranched polylysine fluorescence fibers via wet spinning. (23rd February 2018) - Lu, Hongwei; Zou, Liming; Xu, Yongjing; Sun, Hong; Li, Yan Vivian
Abstract: A simple method of using wet spinning was found effective in the preparation of photoluminescent poly vinyl alcohol (PVA)/hyperbranched polylysine (HBPL) fibers. The photoluminescence of the PVA/HBPL fibers was significantly uniform and the unique uniformity was obtained by controlling the mass ratio of PVA to HBPL in aqueous solutions used in the wet spinning process. The high solubility of HBPL in water make it feasible to well control in the mass ratio of PVA to HBPL, which facilitated the formation of a unique PVA/HBPL mixture, resulting in the fabrication of homogeneous PVA composite fluorescence fibers. The composite fibers exhibit good mechanical, and thermal properties that make the PVA/HBPL fluorescent fibers a great material potentially used in fluorescence applications including optics, imaging and detection.